Social Value Orientation Effects On Adolescents Friendship Quality - Syiva Fitria; Sabine Peters (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2019)
The current study intended to explore the association between Social Value Orientation (SVO) and friendship quality in adolescence, the development as well as gender and age differences. Participants between ages 12 and 25 (N = 292) completed a series of games to measure their SVO and Friendship Quality Scale in order to assess their friendship quality. Analysis of covariance confirmed that SVO did not affect friendship quality. No age and gender differences were found in SVO. However, the results revealed that there was a significant gender difference in friendship quality, where girls have higher positive friendship quality. There was also an age effect on friendship quality, such that, as age increased, negative friendship quality decreased. In conclusion, there was no evidence that SVO influences someone friendship quality. It is possible that SVO only influences the number of friends that someone has.